H-infinity Control Design for Time-Delay Linear Systems: a Rational Transfer Function Based Approach - Korogui, Rubens H. [UNESP]; Fioravanti, Andre R.; Geromel, Jose C.; IEEE (Ieee, 2011)
The aim of this paper is to cope with the H-infinity control synthesis for time-delay linear systems. We extend the use of a finite order LTI system, called comparison system to H-infinity analysis and design. Differently from what can be viewed as a common feature of other control design methods available in the literature to date, the one presented here treats time-delay systems control design with classical numeric routines based on Riccati equation and H-infinity theory. An illustrative example and a practical application involving a 3-DOF networked control system are presented.